Sphingomonas: from diversity and genomics to functional role in environmental remediation and plant growth. (17th February 2020) - Asaf, Sajjad; Numan, Muhammad; Khan, Abdul Latif; Al-Harrasi, Ahmed
Abstract: The species belonging to the Sphingomonas genus possess multifaceted functions ranging from remediation of environmental contaminations to producing highly beneficial phytohormones, such as sphingan and gellan gum. Recent studies have shown an intriguing role of Sphingomonas species in the degradation of organometallic compounds. However, the actual biotechnological potential of this genus requires further assessment. Some of the species from the genus have also been noted to improve plant-growth during stress conditions such as drought, salinity, and heavy metals in agricultural soil. This role has been attributed to their potential to produce plant growth hormones e.g. gibberellins and indole acetic acid. However, the current literature is scattered, and some of the important areas, such as taxonomy, phylogenetics, genome mapping, and cellular transport systems, are still being overlooked in terms of elucidation of the mechanisms behind stress-tolerance and bioremediation. In this review, we elucidated the prospective role and function of this genus for improved utilization during environmental biotechnology.